Prediction Primary Available Blend Biodiesel of Waste Oil from Aurantiochytrium sp. for General Diesel Engines - Tsai, Shu-Yao; Lin, Hsiang-Yu; Lu, Guan-Yi; Lin, Chun-Ping (Advances in Technology Innovation, 2017)
Chemical and enzyme transesterification were compared by discussing preliminary transesterification of waste oil of Aurantiochytrium sp., which was then used in transesterification for the primary available blend biodiesel for a general diesel engine in this study. We made progress on the winterized characteristics of the waste oil’s biodiesel of Aurantiochytrium sp. and its biodiesel, which included the reactivity parameters and properties. This approach led to the development of a novel idea for the evaluation of kinetic parameters of winterization, along with obtaining the suitable operation and storage conditions of biodiesel. Therefore, the waste oil of Aurantiochytrium sp. could be developed for biodiesel production and successfully made into a suitable blend diesel. Overall, we acquired the best condition of mixtures and the highly mixed rate of petrodiesel: biodiesel = 80 : 20 (activation energy of winterization 21.32 kJ/mol; onset temperature of winterization -4.15 °C; heat of combustion 43.15 MJ/kg; kinematic viscosity 3.51 mm2/s; flash point 67.5 °C), which was an appropriate blend biodiesel from the waste oil’s biodiesel of Aurantiochytrium sp.